PENENTUAN HARGA JUAL DENGAN METODE ENTONG PADA PENJUAL JENANG (Studi Fenomenologi Pada Penjual “Jenang” Desa Ngembul Kecamatan Binangun) - Arif Wahyudi; Endah Masrunik (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2019)
This research aims to understand the method for determining price which is applied by jenang (mixed porridge) seller in Ngembul Village Binangun District in Blitar City. Therefore, by using this method which is acceptable with the particular price and does not effect for losing the profit of seller as well as it can be competitive in the market. The method uses qualitative approach and focused on phenomenology. The researcher analyzes the data, ways, attitude and phenomena which are obtained from the object studied (mixed porridge) seller. The result of this study shows that the seller determines the price by using entong (special spoon for taking the porridge). The seller thinks that from all tolls, the entong is the best spoon used to fill all the kinds of the expenditures. Although, there are some differences of each spoons that are applied, but those are not the big problems for the seller and the buyer because it’s differences are not too much.